Assessment of the impact of the Ghana Strategy Support Program, 2005-2008 - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The Ghana Strategy Support Program (GSSP) aims to build the capacity of agricultural stakeholders in Ghana to develop and implement agricultural and rural devel-opment policy reforms. This summary outlines findings from an IFPRI-commissioned assessment of the GSSP's performance from 2005 to 2008, which examined such factors as awareness of and comprehension of the pro-gram and its goals among intended beneficiaries, policy changes and other outcomes resulting from the program, and lessons learned.